Neither First, nor Second, nor… in his Commentary on the Sentences. Francis of Marchia’s intentiones neutrae - Duba, William (Quaestio, 2010)
Abstract In a recent monograph, Sabine Folger-Fonfara introduces neutral intentions as the crowning achievement of Francis of Marchia’s metaphysics. Neutral intentions express the common characteristics of first intentions (pertaining to real beings) and of second intentions (mental beings) and therefore play the role of supertranscendentals. The doctrine of neutral intentions also explains how, in Francis of Marchia’s theory of general metaphysics, being can have maximum extension. Yet this signal development in the history of philosophy does not appear in Francis of Marchia’s main philosophical work, his Commentary on the Sentences. This paper analyzes Francis of Marchia’s doctrine of intentionality in the Quodlibet and compares it to the treatments in the Questions on the Metaphysics and in the Commentary on the Sentences, and concludes that the doctrine of intentionality assumed by Questions on the Metaphysics and articulated by the Commentary on the Sentences reflects a more sophisticated understanding of the problems involved; intentions neutrae themselves can be found in the Sentences under the guise of rationes neutrae, formal characteristics of things considered independently of their presence to the mind.